(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
A job seeker needs to possess a number of skills for being employed in reputed companies. In the present scenario he has to be a good communicator of ideas and concepts in the communicative language, English. Reasoning Abilities, Verbal Aptitude Communicative Competency, Numerical Ability etc. enable the prospective candidates get better employment opportunities. Training the outstanding students to deliver impromptu talks, short speeches, and taking part in Dialogues and Group Discussions will equip them with confidence to face the interviews. Personality traits are well-formed with the development of Life Skills and Soft Skills. Job aspirants have to develop problem-solving abilities, critical and creative thinking to find out solutions in critical situations. Interpersonal relationships are to be established and candidates should be acquainted with the four major skills of language viz. Listening, Speaking, Reading and Writing. Listening to the speeches of eminent literateurs and talks by industry professionals will create awareness as to what is required of them. While at college or university the candidates should utilize the opportunities to acquire the relevant skills, in addition to achieving Academic Excellence to be placed in lucrative positions.